The Role of Cognitive Reserve as Measured by Cognitive Reserve Index Questionnaire Indonesia Version in Geriatric Delirium Cases - Profitasari Kusumaningrum; Dewanto Andoko; Charles Evert Damping; Martina Wiwie Setiawan Nasrun (Faculty of Medicine Universitas Indonesia, 2021)
Delirium is often associated with factors that worsen the condition and prognosis of a person's health. The Cognitive Reserve Index questionnaire Indonesia version (KICK) is a questionnaire that quantifies the cognitive reserve (CR) into a single index. This study aims to obtain an instrument to assess CR, namely KICK, and test its validity and reliability and finding the role of CR in geriatric delirium cases. The study was conducted in the integrated geriatric outpatient and acute geriatric inpatient of Cipto Mangunkusumo Hospital on June 2019 to September 2019, by validity testing and case control study in geriatric delirium cases to 33 subjects with delirium and 33 controls. Content validity test was carried out through a panel test with the conclusion that KICK is relevant for use as an instrument to examine CR. The construct validity of the three variables showed significant correlation with total score with p-value <0,001). Reliability test showed Cronbach’s Alpha of 0,688. Significant differences in CR score of delirium versus control (p<0,01) with OR 9 (95% CI 2.86 to 28.22).KICK is valid and reliable to measure CR of Indonesian elderly and patients with low CR score have a higher chance of developing delirium.